On the Crisis of Political Judgement - Lo Giudice, Alessio (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
Within the technological society the political judgements seem the expression of an emotion. But is this still a political judgment? Could the apparent freedom of the emotional reaction be considered as a case of political freedom? Or, on the contrary, the political freedom is on the field just when an appropriate political judgment, founded on a critical deliberation, is possible? In order to answer to these questions, the paper aims at analysing the conceptual structure of the political judgment and the relationship between freedom and thought implied by such a structure. The purpose is to grasp the deep change (crisis) of the political judgement caused by the impact of new media technologies. Theoretical support will be looked for in Hannah Arendt’s theory of political judgement. Keywords: Judgment, Politics, Freedom, Culture, Arendt.